Remotely Control Wireless Movable Spotlight - Li, Kho Wan; Zainal Abidin, Zuhairiah (Evolution in Electrical and Electronic Engineering, 2020)
Remotely control wireless movable spotlight is one of a wireless power transfer that transmits power without connecting wires. Movable spotlight has some limitation in user design, which is the limited distance to adjust the movable spotlight position. This project was developed using near-field transmission concepts to solve distance limitation for the movable spotlight. A servo motor was used to improve the spotlight position at 0°, 90° and 180° angles. The servo motor was connected to a NodeMCU ESP8266 and controlled by Blynk app. Transmitter circuit consists of a transmitter coil and an oscillator circuit with a maximum working frequency of 180 kHz. Besides, the receiver circuit also has the receiver coil and a full bridge rectifier circuit. It shows that the remote control wireless movable spotlight is more convenient for users where it can be adjusted to the desired position using the Blynk app.